A Compressible Conserved Discrete Unified Gas-Kinetic Scheme with Unstructured Discrete Velocity Space for Multi-Scale Jet Flow Expanding into Vacuum Environment (Communications in Computational Physics, 2020)
The mechanism of jet flow expanding into vacuum environment (or extremely low density environment) is important for the propulsion unit of micro-electro-mechanical systems (MEMS), the thruster of spacecraft, the attitude control system ofsatellite, etc.. Since its flow field is often composed of local continuum region and local rarefied region, the jet flow into vacuum has noteworthy multi-scale transportationbehaviors. Therefore, the numerical study of such flows needs the multi-scale schemeswhich are valid for both continuum and rarefied flows. In the past few years, a seriesof unified methods for whole flow regime (from continuum regime to rarefied regime)have been developed from the perspective of the direct modeling, and have been verified by sufficient test cases. In this paper, the compressible conserved discrete unifiedgas-kinetic scheme is further developed and is utilized for predicting the jet flows intovacuum environment. In order to cover the working conditions of both aerospace andMEMS applications, the jet flows with a wide range of inlet Knudsen (Kn) numbers(from 1E-4 to 100) are considered. The evolution of flow field during the entire startupand shutdown process with Kn number 100 is predicted by the present method, andit matches well with the result of analytical collisionless Boltzmann equation. For Knnumbers from 1E-4 to 10, the flow field properties such as density, momentum, andpressure are investigated, and the results are provided in details, since the publishedresults are not sufficient at the present stage. The extent and intensity of the jet flowinfluence are especially investigated, because they are strongly related to the plumecontamination and momentum impact on objects facing the jet, such as the solar paddles which face the attitude control thruster during the docking process.
Keywords: Multi-scale flow; unstructured velocity space; unified methods; jet flow; vacuum.